Proceedings of the International Conference "Supporting the Forest Sector Reform in Russia and in the Southeast European Countries by Assessing the Experiences of the New EU Member States". Pushkino 21-22nd March 2007 : A contribution to the implementation of the Ministerial Conference on the Protection of Forests in Europe Resolution H3 on Forestry Cooperation with Countries with Economies in Transition - (:unkn) unknown (Metsäntutkimuslaitos, 2007)
The object of the conference was to discuss the various choices of strategy in forest policy, administration and financing made in the transition countries in Central and Eastern Europe, in Russia and in some countries of the Commonwealth of Independent States after the collapse of the Soviet Union.
Materialy mezzhdunarodnoj konferencii Podderzhka reform v lesnom sektore Rossii i stran Jugo-Vostochnoj Evropy opytom stran - novyh chlenov Evrosojuza, Pushkino 21-22.3.2007
Also available in Russian http://urn.fi/URN:ISBN:978-951-40-2083-4 - Published in collaboration with Finnish Forest Research Institute Metla, All-Russion Institute for Continuous Education in Forestry ARICEF and Ministry of Agriculture and Forestry of Finland.
Keywords: Venäjä; Kaakkois-Eurooppa; proceedings; metsätalous; Venäjä; kokousjulkaisut; siirtymätalous